What happens when forced migrants and transit state actors meet? Encounters at decision nodal points during the migration journey - Netta Moshe; Dan Miodownik; Shaul R. Shenhav (Comparative Migration Studies)
Abstract This study investigates the interactions of forced migrants with state actors in transit countries at critical decision nodal points (DNPs) along their journey—defined as turning points where migrants make decisions about resuming mobility or altering the course of their journey. Granted official legal power by the state, transit state actors operate on the ground in various ways using their power. Nevertheless, their roles in the decision-making as experienced by forced migrants have been studied very little. We examine the journey narratives of forced migrants originating from Eritrea and Sudan. We quantitatively identify and analyze spaces of mobility, immobility and DNPs, within their trajectories. The findings demonstrate that state actors in transit countries can serve as integral and concrete journey components that shape migration outcomes. The study concludes by presenting two insights into (i) the directionality of influence (enabling versus halting journey plans) and (ii) the encounter space (direct-official spaces versus indirect spaces).